(untitled) (Libellarium: journal for research in the field of information and related sciences, 2016)
The aim of this article is to analyse the possibilities (and intentions) of Lithuania’s literary periodicals to start publishing them only in a digital version. An assumption is made that network society, affected by fast consumption trends, is more likely to choose digital magazines and newspapers, therefore literary publications are also challenged to reconsider their publishing strategies. There are several very important reasons (small circulation, possibility to survive only with the help of support funds are included) why literary periodicals should think about the possibility to abandon traditional print editions, leaving only a digital version. The attitude of editors of literary publications to possible (or necessary) typological changes could be summarized in a few sentences: the biggest problem – getting (not earning!) more money. The rest is all right. In order to find out what editors of popular periodicals think about these issues the author of this paper interviewed three editors-in-chief. Why popular publications are marched with literary ones? Because they have to survive knowing that they will not get any financial support from anywhere. There was another reason for inquiring the editor-in-chief of delfi.lt, the biggest Lithuanian news portal, about this matter: delfi.lt would like to co-operate with literary publications. Opinion of the deputy editor-in-chief of internet daily bernardinai.lt which publishes many texts on literary subjects was also sought out. What is their opinion?